2018
DOI: 10.3390/molecules23123255
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoresponsive Material of AIE-Active 1,4-Dihydropyrrolo[3,2-b]pyrrole Luminophores Bearing Tetraphenylethylene Group with Rewritable Data Storage

Abstract: A new tetraphenylethylene (TPE) functionalized 1,4-dihydropyrrolo[3,2-b]pyrrole derivative (APPTPECN) was synthesized with obvious aggregation-induced emission (AIE) active by simple synthetic method. APPTPECN exhibited reversible mechanofluorochromic (MFC) behavior. The powder X-ray diffraction (PXRD) and scanning electron microscopy (SEM) investigations exhibited that the MFC nature is originated through a conversion from the microcrystalline to amorphous phase under the stimulus of external force. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“… 13 This situation changed dramatically in 2013, when we serendipitously found a method that allows rapid access to 1,4-dihydro-tetraarylpyrroles[3,2- b ]pyrroles (TAPPs). 14 Since then, TAPPs have found multiple applications in research related to studying symmetry-breaking in the excited state, 15 two-photon absorption, 16 solvatofluorochromism, 13c , 13d direct solvent probing via H-bonding interactions, 17 photochromic analysis of halocarbons, 18 organic field-effect transistors, 19 dye-sensitized solar cells, 20 bulk heterojunction organic solar cells, 21 organic light-emitting diodes, 22 resistive memory devices, 23 aggregation-induced emission, 24 and MOFs. 25 It has been also shown that TAPPs are an excellent platform for the synthesis of the π-expanded heteroanalogues of polycyclic aromatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“… 13 This situation changed dramatically in 2013, when we serendipitously found a method that allows rapid access to 1,4-dihydro-tetraarylpyrroles[3,2- b ]pyrroles (TAPPs). 14 Since then, TAPPs have found multiple applications in research related to studying symmetry-breaking in the excited state, 15 two-photon absorption, 16 solvatofluorochromism, 13c , 13d direct solvent probing via H-bonding interactions, 17 photochromic analysis of halocarbons, 18 organic field-effect transistors, 19 dye-sensitized solar cells, 20 bulk heterojunction organic solar cells, 21 organic light-emitting diodes, 22 resistive memory devices, 23 aggregation-induced emission, 24 and MOFs. 25 It has been also shown that TAPPs are an excellent platform for the synthesis of the π-expanded heteroanalogues of polycyclic aromatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…Then the letters “DCM” could be written with a stick and be wiped off by swabbing or heating measures ( Figure 3 d). 39 …”
Section: Resultsmentioning
confidence: 99%
“…Then, the fluorescent letters could be easily erased by fuming with DCM for a few minutes; after that, the letters could be rewritten with a rod and wiped off again, and the writing/erasing process could be repeated many times. Therefore, this material shows great potential for applications on rewritable paper [ 40 ].…”
Section: Resultsmentioning
confidence: 99%